Evaluation of the antinociceptive activity of Ficus deltoidea aqueous extract. - Sulaiman, Mohd Roslan; Hussain, Mohd. Khairi; Zakaria, Zainul Amiruddin; Somchit, M.N.; Moin, Saidi; Tengku Mohamad, Tengku Azam Shah; Israf Ali, Daud Ahmad (Elsevier, 2008)

(untitled)
The aqueous extract of Ficus deltoidea leaves was evaluated for possible antinociceptive activity in three models of nociception, namely, acetic acid-induced abdominal writhing, formalin and hot plate test. The results of the present study showed that intraperitoneal administration of the F. deltoidea leaves aqueous extract at the dose of 1, 50 and 100 mg/kg, 30 min prior to pain induction produced significant dose-dependent antinociceptive effect in all the models used, which indicating the presence of both central and peripherally mediated activities. Furthermore, the antinociceptive effect of the extract in the formalin and hot plate test was reversed by the non-selective opioid receptor antagonist naloxone suggesting that the endogenous opioid system is involved in its analgesic mechanism of action. Thus, the present results demonstrated that F. deltoidea leaves aqueous extract contains pharmacologically active constituents which possess antinociceptive activity justifying its popular therapeutic use in treating conditions associated with the painful conditions.